Choose to test: self-selected testing for sexually transmitted infections within an online service. (5th March 2019) - Syred, Jonathan; Holdsworth, Gillian; Howroyd, Chris; Spelman, Kez; Baraitser, Paula
Abstract : Objective: To describe the outcomes of user-led, choice of test within an online sexual health service. Methods: We analysed routinely collected data from a free, online sexual health service in Essex, UK that enabled users to select their tests. The service website provided information on all sexually transmitted infections, recommended a testing package based on sexuality and ethnicity, and invited users to modify this if they chose. Data on orders were analysed for the 6 months before (May–October 2016) and after (October–April 2017) implementation. Results: We compared 7550 orders from 6253 users before and 9785 orders from 7772 users after implementation. There was no difference in the proportion of chlamydia (p=0.57) or gonorrhoea (p=0.79) tests that were positive between the two periods. HIV and syphilis positives were too few in our sample during both periods for analysis. During implementation, men who have sex with men (530 users) were offered genital, rectal and oral chlamydia and gonorrhoea testing plus HIV and syphilis testing. In 17.2% of orders, users removed tests. Black or ethnic minority users excluding those who reported as men who have sex with men (805 users) were offered chlamydia, gonorrhoea and HIV testing. In 77.9% of orders, users added a test. All other users were offered chlamydia and gonorrhoea tests only. In 65.2% of orders, users added tests. We observed a reduction in orders of 3083 blood tests (31%). Conclusion: Users engaged with the 'choose to test' intervention. Although a majority added tests, the intervention was cost saving by reducing the HIV and syphilis tests ordered.